HUBUNGAN PELATIHAN, PENGAWASAN, DAN SOSIALISASI KEBIJAKAN K3 TERHADAP KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA STRUKTUR BALOK PROYEK PT X 2021 - Thianamira Nur Pratiwi, (2021)
Personal protective equipment (PPE) is a piece of equipment to decrease the danger of work accidents. In addition, the discipline factor or culture of being obedient in using PPE by workers is important for workers in doing their jobs. By implementing this compliance, it becomes a form of responsibility by the company and workers in order to avoid the dangers that exist in the workplace. The purpose of this study was to analyze the relationship between training, supervision, and socialization of OHS policies on compliance with the use of personal protective equipment (PPE). This type of research is quantitative analytic with a cross-sectional design. The sampling technique used was Total Sampling with a sample of 63 workers of the PT X 2021 project beam structure. The data were obtained by distributing questionnaires and observing in the work area and the data analysis used was Chi-Square. The results showed that the frequency of compliance with using PPE for the beam structure workers of the PT X 2021 project was 73.0%. The results of statistical analysis showed a significant relationship, including training (p-value = 0.000, OR: 34.400), supervision (p-value = 0.000, OR: 19.680). There was no significant relationship between OHS policy and compliance with the use of PPE (p-value = 0.151, OR: 0.366). Therefore, the company is expected to be able to quantitatively and qualitatively increase activities related to training and supervision in increasing the frequency of workers to have a compliant culture using personal protective equipment (PPE).